Correlations between tomographic findings related to degenerative changes, condylar excursions and position, and pain symptomatology in temporomandibular disorders - Esdras F de Carvalho; Israel Chilvarquer; João Gualberto Cerqueira Luz (Wolters Kluwer Medknow Publications, 2018)
Aim: This study analyzed possible correlations between tomographic findings related to degenerative changes and condylar excursions and position with pain symptomatology in temporomandibular disorders (TMD). Materials and Methods: Sixty patients (40 women and 20 men; mean age: 37.9 years) with a diagnosis of TMD, according to the Diagnostic Criteria for Temporomandibular Disorders, were evaluated. The data of their tomographic examinations were retrieved in relation to their degenerative changes, estimations of condylar excursion, and condylar position. Associations between the variables were analyzed using the chi-square test (P ≤ 0.050). Results: There was a predominance of myopain (M) (35% left side), which was followed by arthralgia plus disc displacement (ADD) (23% left side) and latter myopain plus arthralgia and disc displacement (MADD) (18% left side). Regarding the degenerative changes, there was the predominance of flattening (100%), which was followed by sclerosis (85%). The estimation of condylar excursion was more frequent in the hyperexcursion form, followed by the normoexcursion form, and the hypoexcursion form, all on both sides. The position of the condyle was predominantly posterior and less frequently anterior, and there were few cases in the equidistant position. Considering the sides independently, hyperexcursion and MADD were correlated to the left side. For the total sample, condylar hyperexcursion and ADD, and also sclerosis and MADD, were correlated. There was no correlation between condylar position and symptomatology. Conclusion: There was a correlation between hyperexcursion and symptomatology, especially articular, few correlations between degenerative changes and symptomatology, and no correlation between condylar position and symptomatology.